Segre-bag: revolutionizing waste management through innovative segregation - Mohd Puaad, Muhammad Bazli Faliq; Che Hasan, Asmawati; Suhaimi, Azrina; Ismail, Herda Balqis; Martin, Juliana; Hasbullah, Mohd Amran; Salleh, Mohd Zulkhairi (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Waste management in densely populated countries faces significant challenges due to rapid population growth. Among the crucial techniques, waste segregation stands out as a key strategy. In Malaysia, municipal solid waste, especially from offices and homes, has posed environmental concerns, notably with poorly managed plastic and paper waste. The lack of consumer motivation in waste sorting stems from the perceived time and labor intensiveness of segregation processes. This study focuses on evaluating the efficiency of Segre-Bag, an innovative waste segregation tool, in managing and separating trash at UiTM Pasir Gudang. Segre-Bag utilizes three colored plastic bags, each representing a specific type of waste as per Malaysia's government-issued color code for waste segregation. The aim is to streamline waste sorting, reducing time and energy for consumers both in office and household settings. Our findings demonstrate that Segre-Bag significantly aids consumers in simplifying waste segregation processes. By providing a user-friendly method aligned with established waste categories, Segre-Bag enhances waste management efficiency. This research contributes valuable insights into improving waste segregation practices, offering a practical solution to address environmental challenges associated with poorly managed waste streams, particularly plastic and paper waste.